Design of Interactive Learning Media With The Think Talk Write Strategy on The Material of Writing Expository Texts For Grade 10 Vocational High School Students - Konradus Silvester Jenahut; Osniman Paulina Maure (Departement of Mathematics Education, 2022)
This research and development stems from the problem of students experiencing difficulty in expressing ideas or thoughts when composing expository texts. This is due to various factors, such as students having limited practice in writing expository texts and the limited availability of learning sources and supporting media. This research aims to design and develop a learning media product using the Think Talk Write strategy on the subject of writing expository texts. The learning media product is developed by implementing the steps of the 4D model development procedure, which are Define, Design, Develop, and Disseminate. The developed media product is then tested for its level of validity through a validity test by experts and practitioners. The results of the product validity test show that the average percentage score obtained is 85.07% with the category of